PENGARUH SERVICE QUALITY DAN PRODUCT QUALITY TERHADAP LOYALITAS DAN KEPUASAN KONSUMEN PADA AGROWISATA PULESARI, SLEMAN, DIY - Pandu Kusuma Jati; Uswatun Chasanah; Anas Hidayat (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
The goal of this research was to discover the impact of product quality and service quality on loyalty and customer satisfaction. Product quality and service quality are the independent variabels which influence user loyalty in an integrated manner. The researchers employed an intervening variable which is customer satisfaction. This study used a questionnaire survey for carrying out the data of research. Simple random sampling was used as a technique for determining of 275 respondents as the number of samples in this research. The researchers employed Path Analysis as the analysis method in this study. The SPSS Version 23.00 was used as tool for testing the data. Based on Kolmogorov-Smirnov test, all data were normally distributed as the results of the normality test conducted. Meanwhile, the items in all variables are valid based on the results of Pearson Correlation as the validity test and the researchers employed the Cronbach's Alfa test for testing the reliability whose values are seen. There are three tests for testing the hypothesis such as t-test, F test, and R Square in this study. The results show that all are accepted. Customer loyalty and customer satisfaction are affected by product quality and service quality. And, the effect of service quality and product quality on consumer loyalty is also proven mediated by customer satisfaction